2007
DOI: 10.1007/s00595-006-3448-6
|View full text |Cite
|
Sign up to set email alerts
|

The Variations in the Immunologic Features and Interleukin-6 Levels for the Surgical Treatment of Cardiac Myxomas

Abstract: Patients with cardiac myxoma should therefore be operated on immediately because the possibility that the tumor size might be large when IL-6 and/or alpha1-globulin values are high. In addition, cases of "familial myxoma" require careful observation and periodic echocardiography after surgery to identify any possible recurrence. Recently, molecular genetic analyses are therefore considered to be an important diagnostic tool for cardiac myxoma, especially "familial myxoma." Our "familial myxoma" case demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Cardiac arrhythmias, atrial fibrillation, and atrial flutter reportedly occur in approximately 20% of patients with cardiac myxoma. 16,19 In our series, 69% of patients presented with arrhythmia or palpitation. Embolic phenomena are reported in approximately 35% of left-sided and 10% of right-sided myxomas.…”
Section: Discussionmentioning
confidence: 59%
“…Cardiac arrhythmias, atrial fibrillation, and atrial flutter reportedly occur in approximately 20% of patients with cardiac myxoma. 16,19 In our series, 69% of patients presented with arrhythmia or palpitation. Embolic phenomena are reported in approximately 35% of left-sided and 10% of right-sided myxomas.…”
Section: Discussionmentioning
confidence: 59%
“…The constitutional symptoms and signs are fever, fatigue, weakness, weight loss, anemia, arthralgia, and myalgia. Some investigations have revealed that it is associated with an immunologic basis, especially with high values of interleukin-6 in plasma [19-21] . In addition, unknown factors may also affect this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Non-specific constitutional symptoms such as fever, lethargy, physical weakness, fatigue, anorexia, painful erythema, loss of weight and appetite, are seen in up to 90% of cases due to autocrine cytokine production such as IL-6 and IL-8 [8,36]. Non-specific laboratory findings such as chronic hemolytic anemia and thrombocytopenia (due to cellular destruction caused by abnormal blood flow across the tumor surface), polycythemia, erythrocytosis and leukocytosis, raised erythrocyte sedimentation rate, serum C -reactive proteins and immunoglobulins may also be seen in some CM [37,38].…”
Section: Cardiac Myxomasmentioning
confidence: 99%
“…Increased expression of MUC1, IL6 and α1-globulin in CM is associated with increased risk of embolization [36,101]. Recently plakophilin-2 has been identified as adherens junction protein in CM [104].…”
Section: Molecular Genetics Of Cardiac Myxomasmentioning
confidence: 99%